A NEW SPECIES OF ANISOPTERA (DIPTEROCARPACEAE) - Anwari Dilmy (REINWARDTIA, 1956)
Tree up to 51 m tall, with 30 m straight, cylindrical bole, at 1.20 m about 70 cm in diameter. Crown rather sparse, brownish green. Bark grey brown, fissured, grooves about 7 mm deep; 10-20 mm thick with pale brown, round lenticels, under-bark whitish or straw. Wood straw to very pale pink coloured; sapwood not sharply defined. Branchlets rough, grey-brown, end of branchlets with fine, stellate, light brown hairs. Leaves (adult) glabrous, coriaceous, oblong, 8-11,5 cm long, 3-4 cm wide, top (when dried often plicate) shortly acuminate, acumen acutish, 2-4 mm long, base obtuse or rotundate; upper surface often smooth (or lateral nerves slightly prominulous), midrib impressed; lower surface yellowish brown with very prominent midrib, the c. 15 pairs of lateral nerves prominulous; veins reticulate, hardly prominulous; petioles 2-4 cm long, swollen at the base of the blade, brown (fresh). In fresh condition leaves yellowish green below, with yellow veins above. Infructescense 10 cm long, densely, microscopically, light brown pilose. Fruit wings yellowish green; fruiting calyx tube cup-shaped, 10-12mm in diameter at apex, 5-6 mm high, densely, minutely pilose; wings slightly puberulous on the nerves; the 2 large ones elongate obovate-lanceolate, 9-11 X 1,5 - 2 cm, apex acutish, gradually narrowed towards base; at basal insertion 5-8 mm wide; the 3 smaller wings subulate, linear-lanceolate, 2-4 cm long, 3-4 mm wide, 3-nerved. Free part of nut exceeding for 3-5 mm the rim of the calyx tube, crowned by the remainder of the stylopodium; densely, microscopically, stellated pilose